2013
DOI: 10.1158/1055-9965.epi-13-0337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Weight Loss and Exercise on Insulin-Like Growth Factor-I and Insulin-Like Growth Factor-Binding Protein-3 in Postmenopausal Women: A Randomized Controlled Trial

Abstract: High levels of insulin-like growth factor (IGF)-1 may increase the risk of common cancers in humans. We hypothesized that weight loss induced by diet and/or exercise would reduce IGF-1 in postmenopausal women. Four hundred and thirty nine overweight or obese (BMI ≥25kg/m2) women (50–75 y) were randomly assigned to: i) exercise (N=117), ii) dietary weight-loss (N=118), iii) diet + exercise (N=117), or iv) control (n=87). The diet intervention was a group-based program with a 10% weight loss goal. The exercise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…An increase in the ratio of IGF-1: IGFBP3 has been previously reported with weight loss [47] and was observed for both <10% and >10 % loss groups (Figure 1; Tables 3 and 3A). …”
Section: Resultssupporting
confidence: 76%
“…An increase in the ratio of IGF-1: IGFBP3 has been previously reported with weight loss [47] and was observed for both <10% and >10 % loss groups (Figure 1; Tables 3 and 3A). …”
Section: Resultssupporting
confidence: 76%
“…(30-32,34,35) Our findings here indicate that exercise alone – either by intervention arm, or when stratified by changes in VO2max – had no effect on PEDF, PAI-1 or VEGF. With the exception of PEDF, weight-loss in the exercise arm was not associated with alterations in levels of these analytes.…”
Section: Discussionmentioning
confidence: 61%
“…An alterna tive and more plausible explanation is that the lack of substantial change in some intermediary biomarkers (for example, IGF1) in a cancerprotective direction, in the face of substantial weight reduction, argues against that biomarker being a key intermediary in obesity associated carcinogenesis. One recent large randomized trial of dietary and exercise interventions reported no significant changes in IGF1 and IGFBP3, despite sub stantial reductions in body weight in the experimental groups 113 , leading the authors to remark that: "modi fied IGF1 bioavailability is unlikely to be a mechanism through which caloric restriction reduces cancer risk". 114 .…”
Section: Weight Loss and Cancer-relevant Biomarkersmentioning
confidence: 99%